USING THE GPU TO DETERMINING THE AREA THE FLAME IN THE VISION DIAGNOSTIC SYSTEM - Sawicki, Daniel (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2015)
This paper presents possibility of using GPU to determine the edge of the image pulverized combustion coal. Compared are the operation time and the accuracy of edge detection area of the flame. Used a method based on the active contour model Chan-Vese. The results show that there was a significant acceleration of the operation (up to 400%).